PHYTOSANITARY PERCEPTION OF CASSAVA CROP AMONG PRODUCERS IN AGRICULTURAL SETTLEMENTS IN THE MUNICIPALITY OF AMAPÁ - do Ó Luz, Adriano; Roberta Reis dos Santos, Lana; Helena Tavares da Ponte, Nara (Journal of Interdisciplinary Debates, 2024)
Cassava is an agricultural crop widely cultivated throughout Brazil, from north to south. However, this is due to the fact that it is a crop exploited, for the most part, by the segment of small producers, currently known as family farmers. However, phytosanitary problems can compromise the productivity of this crop. Therefore, due to the relevance of the subject and the importance of cassava farming for the State of Amapá, this work aims to investigate the perception of cassava producers in settlements in the municipality of Amapá regarding the main diseases and pests that affect cassava farming in crops. The work carried out in the two settlements (Piquiá and Cruzeiro) located in the municipality of Amapá. Interviews were carried out with producers using a questionnaire with questions about cassava farmers’ perception of diseases and pests that affect cassava cultivation. The plant health data showed that cassava farmers reported the presence of pests and diseases that affect the crop, such as root rot, shoot fly and thread burning, but they did not practice the main strategies to prevent the proliferation of pathogens and insects.